Characterization of lactic acid bacteria postbiotics, evaluation in-vitro antibacterial effect, microbial and chemical quality on chicken drumsticks - Incili, Gokhan Kursad; Karatepe, Pinar; Akgol, Muzeyyen; Gungoren, Alper; Koluman, Ahmet; Ilhak, Osman Irfan; Hayaloglu, Ali Adnan (Academic Press Ltd- Elsevier Science Ltd, 2022)
The aims of this study were to characterize postbiotics, and to evaluate their antibacterial effects in-vitro and on chicken drumsticks. Postbiotics [Pediococcus. acidilactici (PA), Latilactobacillus sakei/Staphylococcus xylosus (LS)] exhibited strong antioxidant activity, and their total phenolic contents were found as 2952.78 +/- 0.4 and 1819.44 +/- 0.39 mg GAE/L, respectively (P < 0.05). A total of 19 different phenolic and flavonoids were determined in the postbiotics. The results of the study revealed that 5% and 10% postbiotics + EDTA decreased the number of L. monocytogenes nearly 5.0 log10 in 6 h in TSB. S. Typhimurium count in the chicken drumstick decontaminated with 10% PA was found as 2.1 log10 lower than the control group on day 0. L. monocytogenes counts in the chicken drumstick decontaminated with 10% Postbiotics+1% LA groups were found to be 1.1 log10 lower than the control group (P < 0.05). The lowest total mesophilic aerobic bacteria counts in the chicken drumsticks were found in the 10% Postbiotics+1% LA samples, and postbiotics did not change the color properties of the drumstick samples on day 0 (P > 0.05). In conclusion, postbiotics and their combinations with natural preservatives may be an alternative approach to reduce the food-borne pathogens and to extend the shelf-life of poultry meat and meat products.
Keywords: Postbiotics; Characterization; Antibacterial effect; Salmonella Typhimurium; Listeria monocytogenes; Chicken drumstick